The applicability of Islamic criminal law in Brunei Darussalam : problems and prospects - Nurul Akmalina binti Haji Yahya (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Islamic Criminal Law, being a part of Shari'ah, contains efficacious measures to prevent and control crimes. In the scheme of Islamic law of governance, it is an incumbent duty on the executive authorities to implement them as part of their attempt to bring the whole social and individual aspects of human life in line with the requirements of the Shari'ah. We have seen that several countries have embarked on the Islamization of their legal systems including the penal laws. In South East Asia, countries like Malaysia have gradually moved towards the same direction by introducing ta'zir punishments for certain offences as defined by Islamic law; Brunei Darussalam has the same desire. To explore the possibility of such an implementation in Brunei, the study primarily aims at delineating its problems and prospects. To accomplish this, using qualitative methodology, the study addresses three main issues: first, it dispels the myths and misgivings which surround the concept of Islamic punishments, second, it identifies the existing legal hurdles for full application of such punishments in Brunei, and lastly, it explores legislative strategies which make such implementation feasible in the country. The study concludes that for the above dream to become a reality, three things are essential, namely, giving full force to the meaning of the relevant provisions of the constitution relating to Islam; amending several existing laws; and improving the existing legal institutions towards such an end.